Pionirske rastlinske vrste in sukcesija na prodiščih - Geršič, Matjaž (Geografski vestnik, 2010)
The point bars are an example of the environment where the initial stages of primary succession can be researched. The species which have overgrown such an environment are called pioneer plant species. Their characteristics, the way of overgrowing such environments, functional significance and human interference on point bars are presented in this article. The results are based primarily on the analysis of the off-road mapping in nine selected point bars of the upper stream of the Sava River. As a result of our research, a graphic model of succession on the point bars has been created.
Keywords: fizična geografija; physical geography; biogeografija; biogeography; habitati; prodišča; rastlinstvo; Slovenia; Slovenija; Sava